Commemorating home: art as place making, an artist’s narration - Sanathanan, T. (My University, 2015)
The damage coursed by 26 years of armed conflict in its various forms on the social fabric of the Sri Lankan Tamil community has led to the loss of place, as well as displacement of many, compelling individuals to live with traumatic and fragile memories of home. This visual essay foregrounds the changing role of the author’s own artistic practice conceived both as eye witness and facilitator in this context. The essay also explores how anthropological tools and museum techniques are employed to draw audiences into the aesthetics of individual pain connected to experiences of loss and displacement in conflict situation.
Keywords: Aesthetics; Art; Home; Place; Srilanka